Pengaruh Intellectual Capital Dan Good Corporate Covernance Terhadap Nilai Perusahaan - Suryani, Siti; Triyani, Agus (Universitas Dian Nuswantoro, 2024)
The process of value creation in companies has changed a lot along with the development of innovation and science in the industrial world. This research aims to analyze the influence of Intellectual Capital through VAIC TM and GCG through the variables Managerial Ownership, Audit Committee and Independent Commissioners on Company Value through Tobin's Q. Research This is quantitative research using secondary data from the annual financial reports of manufacturing companies listed on the IDX for 2017-2021. The sample taken was 60 manufacturing companies in Indonesia using purposive sampling techniques. The data obtained was then analyzed using descriptive analysis, Multiple Linear Regression Test, T test, coefficient of determination test using SPSS. The results of the research show that Intellectual Capital has a positive effect on Company Value, while GCG through managerial ownership and Independent Commissioners has no effect on Company Value. while the Audit Committee has a negative effect on Company Value. It can be concluded that Intellectual Capital has a positive effect on Company Value. This shows that Intellectual Capital can be a factor that influences company value so that companies must pay more attention to intellectual implementation in order to improve company performance. The research results also show that the Audit Committee has a negative influence on Company Value, while Managerial Ownership and Independent Commissioners have no effect on Company Value. This shows that the more audit committees there are, the lower the company value will be.